Holland‐Frei Cancer Medicine 2017
DOI: 10.1002/9781119000822.hfcm105
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Ovarian, Fallopian Tube, and Peritoneal Cancer

Abstract: Overview Ovarian cancer is one of the most treatable solid tumors, as the majority will respond temporarily to surgery and cytotoxic agents. The disease, however, frequently persists and recurs in 70% of cases, having the highest fatality‐to‐case ratio of all the gynecologic cancers. Ovarian cancer is neither a common nor a rare disease, with a lifetime risk of 1 in 70 and a prevalence in the postmenopausal population in the United States of 1 in 2500, which impact strategies for early detection and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
232
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(241 citation statements)
references
References 250 publications
1
232
0
8
Order By: Relevance
“…It accounts for 4% of all female cancers and 31% of cancers of the female genital tract. Ovarian cancer is the 4th most common cause of death from malignancy in women (2). Almost it can be said that, the ovarian cancer has the widest pathologic variety between gynecological cancers and each pathology has a significant effect on the extent of surgery and follow up.…”
Section: Introductionmentioning
confidence: 99%
“…It accounts for 4% of all female cancers and 31% of cancers of the female genital tract. Ovarian cancer is the 4th most common cause of death from malignancy in women (2). Almost it can be said that, the ovarian cancer has the widest pathologic variety between gynecological cancers and each pathology has a significant effect on the extent of surgery and follow up.…”
Section: Introductionmentioning
confidence: 99%
“…About 10% of the reported cases of ovarian cancer are genetically acquired. 15 Cervical cancer mostly affects the lower part of the uterus, just the spot where it joins with the vagina. Cervical cancer used to be the commonest gynecologic cancer across the globe.…”
Section: Gynecological Cancermentioning
confidence: 99%
“…The commonest examples are: endometrial cancer, ovarian cancer and cervical cancer, while the less common ones are: Fallopian tube, vulva, vagina, uterine wall (sarcoma) and placenta (pregnancy tissue: molar pregnancy). [14][15][16] The most occurring gynecologic cancer is endometrial cancer. Studies have shown that the disease will affect about 2% to 3% of women.…”
Section: Gynecological Cancermentioning
confidence: 99%
“…Benign masses are seen in premenopausal and majority of malignant masses are seen in postmenopausal women. 1 Ovarian carcinomas represents 6 th most common cancer in the females and 4 th leading cause of cancer death in women. 2 Symptoms may include abdominal pain, fatigue, bloating, constipation, urinary symptoms, weight loss etc.…”
Section: Introductionmentioning
confidence: 99%